La industrialización del nixtamal y la elaboración de la tortilla en México - Gómez Galvarriato, Aurora (2022)
Description of the development of the nixtamal industry, which comprises the milling of nixtamalized corn, mecha-nized tortilla processing and the production of nixtamalized corn flour. Based on local innovation, it adjusted to the preferences of domestic consumers, who consume freshly made tortillas. However, with time and global expansion, new types of products emerged, such as the packaged tortilla produced on a large scale, that gradually conquered the domestic market. The relationship between local technological innovation and industrialization in a country like Mexico, where both processes do not usually go hand in hand, highlighted.